A constituição da identidade do professor do Ensino Secundário em Cabo Verde: uma abordagem sócio-histórica - Fortes, Victor Manuel dos Reis Borges (2006)
The objective of this work is to understand the forming process of identity of a highschool teacher in Cape Verde and contribute to promote studies on his role and importance in the construction of the Cape Verde society. With the objective of putting the subject in context, a vast social and historical description of Cape Verde is done. Based on the socio-historical approach, a narrative analysis of the life story of an experienced teacher is done, articulating the identity theory elaborated by Ciampa and the sociohistorical theory elaborated by Vygotsky and the studies about subjectivity that are being improved by Gonzalez Rey. The identity, consciousness, activity, meaning and sense categories appear as guiding axis of the constitution of a unique and real subject that at the same time materializes the universal. The theoretical-empirical analysis confirmed the hypothesis mentioned, implied in the categories and showed that the identity is an unfinished process of continuity, rupture and surpassing the professional and biographical constitution mediate by the sense and meaning that the subject gives to himself, to the world and his place in the world. So, it is considered that the objectives proposed in this study had been widely achieved. However, different possibilities of interpretation and conclusions remain open since identity is a process, is movement which in its study terms aspires only the understanding and a minimum of consensus, and not intend to reach a final, absolute result. The theoretical and social relevance of this work precisely relies on the way these two theories were articulated (identity and subjectivity) and in filling an important space in the Cape Verde literature